Meningkatkan Kemampuan Berhitung Pengurangan Siswa Kelas 1 SD Dengan Metode Bermain Puzzle Matematika di SDN 104202 Bandar Setia - Putri Wirdani; Nur Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to improve the mathematical subtraction calculation ability of class I-A students of SDN 104202 Bandar Setia through the puzzle playing method. The problem in this study is low mathematics learning outcomes. The method used in the study is Classroom Action Research (CAR) as many as 2 cycles. The subjects of this study were class 1-A students at elementary school SDN 104202 Bandar Setia Jl. Terusan Dusun V Bandar Khalipah, Percut Sei Tuan District, Deli Serdang Regency, 2024/2025 Academic Year, totaling 27 students consisting of 10 female students and 17 male students. Classroom Action Research (CAR) improves students' subtraction calculation ability by using the mathematical puzzle playing method of class 1 SDN 104202 Bandar Setia, it can be concluded as follows: